Of Critical Theory and Its Theorists. - Bronner, Stephen Eric (Taylor and Francis, 2013)
Of Critical Theory and its Theorists is an intelligent, accessible overview of the entire Critical Theory Tradition, written by one of the leading experts on the subject. Filled with original insights and valuable historical narratives, Of Critical Theory and Its Theorists covers the work of major philosophical thinkers such as Benjamin, Horkheimer, Adorno, Marcuse and Habermas and revisits the contributions of lesser-known figures such as Karl Korsch and Ernst Bloch. Bronner measures the writing of these theorists against each other, postmodernist philosophers and t.